Quadrilateral Lateral Snake Gluing of Path and Bistar are Prime Cordial Graphs - Tamilselvi, I; Selvaraju, P; Gayathri, S (International Journal of Engineering and Technology, 2018)
The graph is called a Quadrilateral Snake graph. Which is defined as series connection of non-adjacent vertices of â€˜Nâ€™ number of cycleÂ Â Â and these vertex setÂ Â Â and edge setÂ Â are described belowÂ Â Â Figure 1: Quadrilateral Snake graphÂ A prime cordial labeling of a graph G with vertex set V(G) is a bijectionÂ Â Â such thatÂ each edgeÂ Â is assigned the label 1 ifÂ Â and 0 ifÂ Â then the number of edges labeled with 0 and the number of edges labeled with 1 differ by at most 1. A graph which admits a prime cordial labeling is called a prime cordial graph.In this paper we prove that the graphs,Â Â Â Â Â Â